No Trademark Protection for Artworks in the Public Domain – A Practical Guide to the Application of Public Order and Morality as Grounds for Refusal. Issue 1 (12th August 2021) - Senftleben, Martin
Abstract: With its 2017 landmark decision in Vigeland, the Court of Justice of the European Free Trade Association States (EFTA Court) has paved the way for the invocation of public order and morality as grounds for refusal when trademark protection is sought for cultural expressions in the public domain. Dealing with an attempt to register artworks of the famous Norwegian sculptor Gustav Vigeland as trademarks, the EFTA Court took this step to safeguard the public domain status of literary and artistic works after the expiry of copyright, shield cultural creations against 'commercial greed' and ensure the freedom of the arts. 1 Trademark examiners and judges seeking to follow in the footsteps of the EFTA Court, however, may find it difficult to operationalize the Vigeland criteria and put corresponding arguments for refusal into practice. Against this background, the following analysis provides guidelines for the practical application of public order and morality arguments in cultural heritage cases. It describes problems arising from the grant of trademark rights in cultural public domain material (Section I) and the traditional reluctance of trademark offices and courts to rely on public order and morality considerations in this context (Section II). After this statement of the problem, the criteria following from the Vigeland decision will be introduced (Section III) before we explore the practical implementation of the EFTA Court's morality (Section IV) and public order (Section V) arguments in more detail. The final Section VI summarizes the results of the analysis.